KAJIAN PRODUKTIVITAS DAN MUTU TEMBAKAU TEMANGGUNG BERDASARKAN NILAI INDEKS ERODIBILITAS DAN KEPADATAN TANAH - Anam Prasetiyo; D Djajadi; S Sudarto (Jurnal Tanah dan Sumberdaya Lahan, 2016)
This study was aimed to identify the distribution of productivity and quality of Temanggung tobacco, identify relationships between soil erodibility with soil compaction and productivity quality of Temanggung tobacco, and identify relationships between soil erodibility index with productivity and quality of Temanggung tobacco. The study was conducted by field survey method with the object of study was tobacco fields in Temanggung Regency, Central Java. Based on the data obtained, two maps i.e. map of productivity distribution and map of Temanggung tobacco quality. The results showed that the soil compaction affected the value of erodibility index. The higher of the soil compaction, the lower was the value of soil erodibility. It was because the compaction of the soil influenced one aspect of erodibility. The soil compaction affected the productivity but did not affect to the quality of Temanggung tobacco. The more compact the soil, the lower the productivity of the land, it was because root development was hampered by the dense soil, thus affecting the development of other plants (leaves). While erodibility did not affect productivity, it affected the quality of tobacco. The higher erodibility indicated the lower quality tobacco. This was because the high soil erodibility increased soil sensitivity to erosion.